PELAKSAAAN MANAJEMEN ARSIP DALAM MENINGKATKAN EFEKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Reni Juliati; Nifi Lamingthon (JIANA ( Jurnal Ilmu Administrasi Negara ), 2021)
A good filing system is that the archive system must be easy to implement, so that it does not cause difficulties, both in storage and retrieval of the archive. The filing system used must be in accordance with the type and scope of the organization's activities. Although archives play an important role in administration, in reality we still encounter many difficulties faced by the organization when retrieving the required files. The purpose of this study was to determine the implementation of archive management in increasing the effectiveness of employee work at the sub-district office of Tanjung Lago, Banyuasin Regency. This research method uses descriptive qualitative, which is a study by comparing existing theories with the reality in the field, then analyzing them in verbal form. Meanwhile, in collecting data using observation techniques, interviews, and agency documents, as well as data analysis starting from data collection, data presentation, and drawing conclusions. From the results of the study, the conclusions that can be obtained from this research are that the implementation of archive management at the Subdistrict of Tanjung Lago Subdistrict, Banyuasin Regency is optimal by using a manual archive storage system according to the principal where the archive is stored based on the problem, there is no difference between personal archives, free, and confidential because the archive storage is placed in one folder for incoming mail, outgoing mail folders, and others are placed in one file room. And the effectiveness of the work of employees at the Tanjung Lago District Head Office is not yet optimal and improvements are still needed in terms of time for the management of population administration to be faster and more effective.